Baking in the American South : 200 recipes and their untold stories - Byrn, Anne (Harper Celebrate, 2024)
Witness the rise of Southern baking from humble recipes to one of the world's richest culinary traditions in this essential cookbook from bestselling author Anne Byrn. With 200 recipes and hundreds of photos, Baking in the American South has the biscuits, cornbread, cakes, and rolls that will help you bake like a Southerner, even if you aren't.